Polymer-Based Toothpastes and Their Ability in Control Tooth Extrinsic Stain - Garcia, Raissa Manoel; Rigo, Letícia Maria Balbino; Lima, Leonardo Custódio; Sakae, Leticia Oba; Cavalli, Vanessa; Borges, Alessandra Buhler [UNESP]; Scaramucci, Taís (Wiley, 2024)
Objectives: To synthesize experimental toothpastes (ETs) containing four different polymers (sodium linear polyphosphate [LPP]; chitosan [CHI]; sodium hexametaphosphate [HMP]; and sodium pyrophosphate [PP]) and test their ability in preventing and removing tooth extrinsic stain. Methods: The tooth specimens were randomly assigned into six groups (n = 10): control (artificial saliva), regular toothpaste (RT—no whitening claim), ET 5% LPP, ET 0.5% CHI, ET 5% HMP, and ET 5% PP. Each cycle consisted of chlorhexidine (2 min), staining broth (30 min), artificial saliva (30 min), brushing (45 strokes), and artificial saliva (30 min). Color parameters (L*, a*, and b*) were assessed at baseline and after 21 cycles. ΔEab, ΔE00, ΔWID, ΔL, Δa, and Δb were analyzed through ANOVA and Tukey test, at a 5% significance level. Results: ET 5% PP showed lower ΔEab and ΔE00 than the control and RT (p < 0.01). For ΔWID, PP showed a higher value. For ΔL (p = 0.265) and Δb (p = 0.119), there were no significant differences among the groups. For Δa (p = 0.01), ET 5% PP showed a difference with the control. Conclusions: The ETs showed a similar effect in preventing and removing tooth extrinsic stains. However, the sodium pyrophosphate-containing toothpaste was the only one with a superior effect in comparison with RT or brushing without toothpaste. Clinical Significance: The use of toothpastes for managing tooth extrinsic stains is a common approach in dentistry. In addition to the abrasives, their effect can be further enhanced by the presence of some polymers. Toothpastes containing sodium pyrophosphate demonstrated a superior ability to control tooth extrinsic stains.
Keywords: chitosan; color; dentifrices; polyphosphates; tooth discoloration